Analysis of The Influence of Minimum Wage and Human Development Index On Unemployment Rate In Indonesia] - Huda, Syamsul; Yuliati, Anik (Devotion : Journal of Research and Community Service, 2022)
One of the many development goals is to improve the performance of the economy in order to be able to create jobs and organize a decent life for all the people which in turn will realize the welfare of the population. The purpose of this study is to determine the effect of the minimum wage on the unemployment rate in Indonesia and to determine the effect of the human development index on the unemployment rate in Indonesia. The method used is quantitative method with multiple linear regression analysis and statistical test using t-statistical test. The results showed that the wage level had a positive and insignificant effect on unemployment. Meanwhile, the human development index has a negative and insignificant effect on unemployment